Atypical Teratoid Rhabdoid Tumor: A Possible Oriented Female Pathology? - Baiano, Cinzia; Della Monica, Rosa; Franca, Raduan Ahmed; Del Basso De Caro, Maria Laura; Cavallo, Luigi Maria; Chiariotti, Lorenzo; Ius, Tamara; Jouanneau, Emmanuel; Somma, Teresa (Frontiers in Oncology, 2022)
Atypical teratoid rhabdoid tumor is a rare lesion that occurs mainly in children can be supratentorial or infratentorial and it accounts for 1-2% of pediatric brain tumors and over 10% of central nervous system (CNS) tumors in infants, with a male preponderance up to 3 years of age, more than 50% of these occur in the cerebellum. In this report we describe four new cases of sellar AT/RTs underwent endoscopic endonasal approach and different adjuvant therapies. Our aim is to report the clinical, radiological and pathological features of these rare lesions, focusing on the possibility to perform an early diagnosis and appropriate therapeutic strategy.